Կոտայքի և Գեղարքունիքի մարզերի լեռնամարգագետնային գոտու հազվագյուտ բուսատեսակների քարտեզագրումը GIS միջավայրում - Համբարձումյան, Ա. Մ. (ՀԱԱՀ հիմնադրամ)
Ուսումնասիրվել է ՀՀ լեռնամարգագետնային գոտու հազվագյուտ 20 բուսատեսակ, առկա տարածական տվյալների բազայի հիման վրա կազմվել են բուսաբանական, տեղագրական, քարտեզագրական, գրաֆիկական բնութագրերը: Հազվագյուտ բուսատեսակների պահպանմանն ուղղված միջոցառումների արդյունավետության բարձրացման նպատակով մշակվել է քարտեզագրման գործողությունների հաջորդականություն (ալգորիթմ), որը կիրառվել է Կոտայքի և Գեղարքունիքի մարզերում աճող հազվագյուտ բույսերի՝ ArcGIS միջավայրում քարտեզագրման համար։ Կենսաբազմազանության տվյալների թարմացման և համալրման նպատակով առաջարկվում է այն կիրառել նաև ՀՀ բնահողային մյուս գոտիները քարտեզագրելիս։ Изучено 20 видов редких растений горно-луговой зоны РА, на основе имеющейся пространственной базы данных составлены их ботанические, топографические, картографические, графические характеристики. Для повышения эффективности мероприятий, направленных на сохранение редких видов растений, была разработана последовательность картографических операций (алгоритм), которая была использована при картографировании в среде ArcGIS редких растений, произрастающих в Котайкской и Гегаркуникской областях. В целях обновления и дополнения данных о биоразнообразии рекомендуется использовать этот алгоритм и для картографирования других природных зон РА. Throughout the current research 20 rare plant species of the RA mountain meadow zone has been studied and the botanical, topographical, cartographical and graphical descriptions have been compiled based on the existing spatial database. At the first research phase, three rare plants growing in the regions of Kotayk and Gegharkunik were mapped in the ArcGIS environment: Inula acaulis Schott & Kotschy ex Boiss., Acanthus dioscoridis and Draba araratica Rupr. For mapping, first their distribution per communities, settlements, operational significance and soil type was studied and identified, then digital mapping and analysis were performed in the GIS (Geographic Information Systems) environment. Based on the results, it was recommended to take appropriate measures for their preservation. Further changes in the ecological condition of rare plants growing in the selected regions were studied, maps of the given areas were drawn up in the GIS environment, and analysis of plant location, growth density, distance from the settlement, functional significance of the land, threats of extinction as a rare plant species, and conservation measures was performed. The received digital maps and analysis of mapping results justify the need for the development of additional measures (legal, economic, environmental). In order to map the mentioned plant species in ArcGIS environment, sequence of actions has been developed based on which it is possible to update, adjust and complete the database of rare plant species in the mountain meadow zone of Armenia and enrich the global biodiversity repository through the GBIF system.
Keywords: Ագրոնոմիա և ագրոէկոլոգիա